A holistic ecosystem for rural mHealth applications and lesson learnt - Jacey, Lynn Minoi; Mohd Raili, Suhaili; Yeo, Alvin W (IEEE Xplore, 2015)
Delivering mHealth applications requires a mHealth ecosystem and this paper will present the development of an ecosystem of mHealth applications to be deployed at remote and rural villages that do not enjoy the same health benefits as in urban areas. Some evidence was found to indicate advantages of mHealth applications in supporting healthy living and wellness behavioural change among the people. The fundamental principle of an ecosystem is to enhance the participation of all the stakeholders and to understand the big picture of the work process holistically. The stakeholders include developers, telecommunication providers, patients, caregivers, healthcare providers, the Ministry of Health and other government sectors. It is important to balance the commercial interests and the peoples’ needs. For the last decade, commercialised mHealth applications are increasingly available to target heterogeneous audiences and address specific health needs. With that, research interest in mHealth is also increasing together with the complexity of the ecosystems that impact all the stakeholders. We will present the development of protocols and privacy from lessons learnt to increase the effectiveness of mHealth in practice and to allow better understanding for future development and employment. We have also conducted a pilot participatory study at four telecentres at rural areas in Malaysia using commercialised mHealth systems.